2018
DOI: 10.1021/acsami.7b15103
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Dual-Ion Beam Sputter-Instigated Plasmon Generation in TCOs: A Case Study of GZO

Abstract: The use of the high free-electron concentration in heavily doped semiconductor enables the realization of plasmons. We report a novel approach to generate plasmons in Ga:ZnO (GZO) thin films in the wide spectral range of ∼1.87-10.04 eV. In the grown GZO thin films, dual-ion beam sputtering (DIBS) instigated plasmon is observed because of the formation of different metallic nanoclusters are reported. Moreover, formation of the nanoclusters and generation of plasmons are verified by field emission scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…The development and improvement of surface coatings is a major challenge in industry today because materials are used in many strategic sectors, including health, transport, housing, energy, and the production of luxury goods [ 1 , 2 , 3 , 4 ]. Metal oxides are an important class of materials that can meet this need thanks to their chemical, mechanical, and thermal stability, and thanks to their physical and chemical properties (e.g., SiO 2 , ZnO, TiO 2 ) [ 5 , 6 , 7 , 8 , 9 , 10 ]. Titanium dioxide (TiO 2 ) is the best known and most widely used of these oxides to date.…”
Section: Introductionmentioning
confidence: 99%
“…The development and improvement of surface coatings is a major challenge in industry today because materials are used in many strategic sectors, including health, transport, housing, energy, and the production of luxury goods [ 1 , 2 , 3 , 4 ]. Metal oxides are an important class of materials that can meet this need thanks to their chemical, mechanical, and thermal stability, and thanks to their physical and chemical properties (e.g., SiO 2 , ZnO, TiO 2 ) [ 5 , 6 , 7 , 8 , 9 , 10 ]. Titanium dioxide (TiO 2 ) is the best known and most widely used of these oxides to date.…”
Section: Introductionmentioning
confidence: 99%
“…Complex chalcogenide compounds have interesting chemical and physical properties and the materials are widely used in modern optical and electronic technologies [1][2][3][4][5][6][7][8][9][10]. In recent years, complex Cu + -containing sulfides and selenides were considered as promising thin film absorber materials in solar cell structures [11][12][13][14][15][16]. This activated general interest to crystal chemistry and the properties of Cu + chalcogenides, including a search for new materials.…”
Section: Introductionmentioning
confidence: 99%
“…The research detailed herein presents a new sensing approach on ZnO in addition to the conventional sensing techniques described above. Recently, increased efforts have focused on alternative plasmonic materials including Si, III-nitrides, and oxide semiconductors. Surface plasmons on oxide semiconductors (oxide-based SPRs) are expected to be successfully employed for optical applications in the infrared (IR) range. One particularly interesting material is metallic ZnO layers obtained by doping with Ga (Al) impurity atoms, , which have great potential due to their lower optical losses compared with noble metals in the IR range. It has been reported that surface plasmon resonances on the metallic ZnO (ZnO-SPRs) layers and nanostructures are excited from the near- to mid-IR range in terms of propagated- and localized-type surface plasmons, respectively. Of these structures, we have focused on film platforms for the development of biosensing applications with propagated-type SPRs.…”
Section: Introductionmentioning
confidence: 99%